Islamic Classical Texts Learning to Foster Students’ Moderate Attitudes - Lasawali, Adhriansyah A.; Masdul, Muhammad Rizal; Suryadinata, A. Moh. Ickamal; S., Rismawati; Husain, Muhammad Zakir (Al-Hayat: Journal of Islamic Education, 2025)
This study aims to analyse the internalisation of religious moderation at Al-Istiqamah Modern Islamic Boarding School through Islamic classical texts (kitab kuning) instruction amid religious polarisation and contemporary educational demands. The research addresses a gap in previous studies by presenting the integration of traditional and modern methods, a tiered curriculum, and social interaction within the pesantren as contributing factors in shaping moderate attitudes, including freedom in choosing a mazhab, tolerance, and openness. This research employs a qualitative approach with a case study method. This study collected data through observation, in-depth interviews, and documentation, and analysed them through data reduction, data presentation, and verification stages. The findings reveal that kitab kuning learning in this institution is conducted formally in the classroom by modifying traditional methods into modern approaches based on the Tarbiyatul Muallimin al-Islamiyah curriculum. The materials include classical kitab and miniature kitab kuning covering fiqh, usul fiqh, hadith, tafsir, Arabic language, and other Islamic sciences. This process significantly contributes to fostering students' moderate attitudes, as reflected in their freedom to choose a school of thought, tolerance toward differing opinions, decisiveness in religious choices, and openness to interacting with various Islamic organisations. The study offers originality by demonstrating that moderation is shaped not only through curricular content but also through social interaction, teacher role modelling, and students’ autonomy in choosing a school of thought. It also opens pathways for future research, including comparative studies among Islamic boarding schools or investigations into the sustainability of moderation values among alums.